Sexually transmitted infections in HIV-infected patients in Kabale Hospital, Uganda - Michael Odongo Osinde; Othman Kakaire; Dan Kabonge Kaye (Journal of Infection in Developing Countries)
Introduction: Acquisition of sexually transmitted infections (STIs) is an epidemiological marker of high-risk sexual behavior in HIV-infected patients. We assessed the prevalence of STIs among patients attending an HIV care and support centre.